Effects of pitch size and set configuration on mechanical responses and fatigue induced by different small-sided games in soccer - Javier Hidalgo de Mora; Pedro Jesús Cornejo-Daza; Juan Sánchez-Valdepeñas; Luis Rodiles-Guerrero; Javier Riscart López; Miguel Ángel Campos-Vázquez; Fernando Pareja-Blanco (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Physical match actions are simulated through modified games. Pitch size and set configuration seems to influence the physical responses during small-sided games.